Influence of the surface termination on the light emission of crystalline silicon nanoparticles - Botas, Alexandre M. P.
The light emission properties of silicon crystalline nanoparticles (SiNPs) have been investigated using steady-state and time-resolved photoluminescence measurements carried out at 12 K and at room temperature. To enable a comparative study of the role of surface terminal groups on the optical properties, we investigated SiNPs-H ensembles with the same mean NP diameter but differing on the surface termination, namely organic-functionalized with 1-dodecene (SiNPs-C12) and H-terminated (SiNPs-H). We show that although the spectral dependence of the light emission is rather unaffected by surface termination, characterized by a single broad band peaking at similar to 1.64 eV, both the exciton recombination lifetimes and quantum yields display a pronounced dependence on the surface termination. Exciton lifetimes and quantum yields are found to be significantly lower in SiNPs-H compared SiNPs-C12. This difference is due to distinct non-radiative recombination probabilities resulting from inter-NP exciton migration, which in SiNPs-C12 is inhibited by the energy barriers imposed by the bulky surface groups. The surface groups of organic-terminated SiPs are responsible for the inhibition of inter-NP exciton transfer, yielding a higher quantum yield compared to SiNPs-H. The surface oxidation of SiNPs-C12 leads to the appearance of a phenomenon of an exciton transference from to the Si core to oxide-related states that contribute to light emission. These excitons recombine radiatively, explaining why the emission quantum of the organic-terminated SiNPs is the same after surface oxidation of SiNPs-C12.